(untitled) (Journal of the College of Education for Women, 2019)
The subject of youth care of important issues in view of what constitutes the importanceto the development of societies in general and as much as enjoy young people in any societyare good psychological health and agree psychosocial be healthy to be effective to invest theirenergies and their potential for the progress of that society and development of the socialaspects and economic. The universities of the most important educational institutions thatprovide care for young people, they are as well as providing information and expertisenecessary to prepare young people for life and the development of mental abilities, they aredifferent activities that will satisfy their needs physical, psychological, social and working toremove all that would preclude it. That most of the physical problems are of impairmentssenses and disadvantages of physical and deflection physical health has caused among manynarrow psychological young people and not feel good about efficiency and fitness and thusaffect the self-concept among young people adversely affected either psychological problemswhich appear in the form of a sharp emotions and Aztrapat disease and the holding ofpsychological It primarily due to a poor young man agrees with itself and with itsenvironment because of its failure to achieve its goals and satisfy the psychological, physicaland social needs and lead these problems if not resolved to the asylum of the individual tosome defensive tricks to mitigate the severity of tension and frustration As these tricks arebased on distortion Indeed, it may cause the individual who relied upon to stay away fromreality and may end up being a mental illness. As for the social problems it is represented inthe difficulties and the types of deviations in social behavior and manifestations of poor socialharmony experienced by university students. As well as these problems are essentiallydeviations and difficulties linked to relations university youth members and the values andtraditions, customs and laws, and also includes the problem of poverty and lack of financialpossibilities and failure to invest leisure ideal investment through various activities. All ofthese obstacles shift between university students and the achievement of social developmentsense. And that the problems of physical, psychological and social intertwined with eachother and affect negatively on academic achievement for young university must be torecognize these problems and identified for the purpose of helping to find solutions.